Indirect Perpetration Through Organized Power Structures and Co-Perpetration in the Corporate Sphere: A Solution to the Limitations of Chilean Law to Punish the Management Bodies of Companies as Authors? - Contreras Chaimovich, Lautaro Camilo (2022)
In Chilean law, difficulties arise when it comes to ascribing criminal responsibility to corporate management bodies that give orders to their subordinates to commit intentional crimes of domination, which is explained by a variety of reasons, both dogmatic and of positive law. According to the “individual ascription of legal responsibility model”, the direct perpetrator of a crime is the person who carries out both the actus rea and means rea of an offence, without grounds for justificatory or excusatory defenses of guilt. Due to the existing division between making decisions and taking action in the corporate sphere, management bodies do not typically carry out the respective criminal conduct and, consequently, cannot be perceived as principal perpetrators. Moreover, they will often avoid making co-perpetration contributions, as described in article 15, Nos 1 and 3 of the Chilean Criminal Code. On the other hand, it is uncommon for them to use instruments that are not fully responsible for the perpetration of a crime, and thus cannot be considered as principal perpetrators by proxy. Therefore, corporate management bodies may only be held liable as instigators. Furthermore, the approach of German jurisprudence, according to which it is possible to extend the concept of organizational control to the corporate field, and thus punish the superior bodies that issue unlawful instructions as perpetrators by proxy, cannot be accepted in Chilean law; nor can the doctrinal proposal to make managers who order their subordinates to commit crimes liable as co-perpetrators be accepted.